Quantitative assessment of pupillary light reflex for early prediction of outcomes after out-of-hospital cardiac arrest: A multicentre prospective observational study. (October 2018) - Tamura, Tomoyoshi; Namiki, Jun; Sugawara, Yoko; Sekine, Kazuhiko; Yo, Kikuo; Kanaya, Takahiro; Yokobori, Shoji; Roberts, Rachel; Abe, Takayuki; Yokota, Hiroyuki; Sasaki, Junichi
Abstract: Aim: To clarify whether quantitative assessment of pupillary light reflexes (PLR) can predict the outcome of post-cardiac arrest (CA) patients during the first 72 h after the return of spontaneous circulation (ROSC). Methods: Fifty adults resuscitated after non-traumatic out-of-hospital CA (OHCA) (mean age 64.1 years old, 36 males) were enrolled in four emergency hospitals. PLR was sequentially measured at 0, 6, 12, 24, 48, and 72 h after ROSC by an automated portable infrared pupillometry. PLR values for each time point were compared between both survivors and non-survivors, and patients with either favourable (Cerebral Performance Category (CPC) 1 or 2) or unfavourable neurological outcomes. Results: Twenty-three patients survived for 90 days after CA, and 13 patients achieved favourable neurological outcomes. The PLR values of the survivors and patients with favourable neurological outcomes were consistently greater than those of non-survivors (P < 0.001) and those with unfavourable neurological outcomes (P < 0.001), respectively. The change in PLR over time was not statistically different between the outcome groups. The 0-hour PLR best predicted both 90-day survival (AUC = 0.82, cutoff 3%, sensitivity 0.87, specificity 0.80) and favourable neurological outcomes (AUC = 0.84, cutoff 6%, sensitivity 0.92, specificity 0.74). No patient with a 6-hour PLR less than 3% survived for 90 days after CA. Conclusions: Quantitatively measured PLR was consistently greater in survivors and patients with favourable neurological outcomes during the 72 h after ROSC. Quantitative assessment of PLR at as early as 0 h has a potential role for prognostication in post-CA patients.